SP3.1.1 Follow-up After Acute Diverticulitis: Can We Reduce the Burden on Endoscopy Services?. (9th August 2022) - Dean, Harry; Britton, Emily; Farrow, Emily; Abdel-Khaleq, Sameerah; Bradbury, Molly; Cook, Tim
Abstract: Background: Acute diverticulitis (AD) is a common cause of presentation to emergency surgical services. Follow-up with endoluminal investigation to exclude colorectal cancer (CRC) remains controversial. Guidelines are increasingly moving to a more restrictive follow up based on severity of disease and age. The purpose of this study was to assess the prevalence of CRC in AD patients and the impact of follow-up on endoscopy services. Methods: Patients admitted with a diagnosis of AD over a 2-year period were reviewed. The proportion of patients undergoing endoscopic follow-up and the CRC detection rate were recorded. The potential impact of a more conservative approach to follow-up was evaluated. Results: There were 484 patients with AD presenting 546 times (M:F = 198:286; median age = 63 years). 80% of admissions were aged 50 or older. There were 43 emergency interventions in 39 patients (10 percutaneous drain; 33 surgery). The remainder were managed conservatively. 28 patients (5.1%) underwent colonic resection with cancer found in one specimen (3.6%). 286 patients underwent endoluminal follow-up with cancer diagnosed in 3 cases (1.0%). There was no significant difference in the prevalence of CRC between patients requiring emergency surgery and those managed conservatively, or between patients with complicated versus uncomplicated diverticulitis. Conclusion: CRC masquerading as acute diverticulitis is rare. The incidence of neoplasia both at endoscopic follow-up and in patients requiring emergency intervention is low. Conservative follow-up strategies appear safe, but their effectiveness in reducing the burden on endoscopy services may be limited by current age-based recommendations.